An empirical assessment of the sustainable development goals compass based on consumer sentiment. Issue 1 (5th April 2022) - Anwar Abdou, Yasmin; El-Bassiouny, Noha; Becker-Ritterspach, Florian
Abstract : Purpose: This research aims to provide an empirical assessment of consumer sentiment towards corporate sustainability practices in the context of developing countries, specifically Egypt. Design/methodology/approach: A survey was deployed to measure the importance of corporate sustainability activities to consumers. Findings: The results demonstrate that consumers are concerned with all the measured dimensions of corporate sustainability practices, yet some of the dimensions are more critical to them than others. Originality/value: By providing an overview of how consumers' purchase behavior is affected by corporate sustainability practices, this research contributes to knowledge on understanding more about sustainable consumer behavior in developing countries, which is scarce. Moreover, this research goes further by segmenting sustainable consumers into groups based on their sustainability concerns.